First records of Parahelice K. Sakai, Türkay & Yang, 2006 and Pseudohelice K. Sakai, Türkay & Yang, 2006 from Vanuatu, with description of a new species of Parahelice (Crustacea: Brachyura: Varunidae) - Hsu, Jhih-Wei; Shih, Hsi-Te (Zootaxa, 2024)
The genera Parahelice K. Sakai, Türkay & Yang, 2006, and Pseudohelice K. Sakai, Türkay & Yang, 2006, are widely distributed in estuarine, mudflats, or mangroves in the Indo-West Pacific, and species of them are often sympatric. Species identification of the two genera is generally difficult, mainly due to the similar morphology and large intraspecific variation. Our study is the first report of the two genera from Vanuatu, including one new species, Parahelice ngankeeae sp. nov., as well as Par. pilimana (A. Milne-Edwards, 1873) and Pseudohelice subquadrata (Dana, 1851). These species can be distinguished from similar species by the characters of the suborbital cristae, the male chelipedal manus, and the first gonopods. The new species is also supported by the molecular results from the cytochrome c oxidase subunit I (COI).